Hematopoietic target cells of anemogenic subgroup C versus nonanemogenic subgroup A feline leukemia virus. - Dean, G A (1992)
Feline leukemia viruses (FeLVs) belonging to interference subgroup C induce fatal anemia resembling human pure red cell aplasia (PRCA). Subgroup A FeLVs, although closely related genetically to FeLVs of subgroup C, do not induce PRCA. The determinants for PRCA induction by a molecularly cloned prototype subgroup C virus (FeLV-Sarma-C [FSC]) have been localized to the N-terminal 241 amino acids of the surface glycoprotein (SU) gp70. To investigate whether the anemogenic activity of FSC reflects a unique capacity to infect erythroid progenitor cells, we used correlative immunogold, immunofluorescence, and cytological staining to study prospectively the hemopoietic cell populations infected by either FSC or FeLV-FAIDS-61E-A (F6A), a prototype of subgroup A virus. The results demonstrated that although only FSC-infected animals developed erythrocyte aplasia, the env SU and the major core protein (p27) were expressed in a surprisingly large fraction of the lymphoid, erythroid, and myeloid lineage marrow cells in both FSC- and F6A-infected cats. Between days 8 and 17 postinoculation, gp70 and p27 were detected in 43 to 73% of erythroid, 25 to 75% of lymphoid, and 35 to 50% of myeloid lineage cells, regardless of whether the cats were infected with FSC or F6A. Thus, anemogenic subgroup C and nonanemogenic subgroup A FeLVs have similar hemopoietic cell tropism and infection kinetics, despite their divergent effects on erythroid progenitor cell function. Acute anemia induction by subgroup C FeLV, therefore, does not reflect a unique tropism for marrow erythroid cells but rather indicates a unique cytopathic effect of the SU on erythroid progenitor cells.